Junior High School Students Ability to Use The Polya’s Step to Solve Mathematical Problems Through Problem Based Learning - Muhammad Royani; Winda Agustina (International Journal of Trends in Mathematics Education Research, 2019)
This study purpose to determine the ability of students to use Polya’s step in solving mathematical problems through Problem Based Learning. This study used a quantitative approach with a total sample, as many as 26 students of 7th grade of Junior High School 2 Kusan Hulu student. Problem Based Learning activities held in four meetings and two tests. The test results were analyzed based on the Polya’s problem solving steps, calculated with the percentage in each step. The results showed that the ability of junior high school students to use Polya’s steps in solving mathematical problem through Problem Based Learning was: 1) ability to understand problems at 83.80%, 2) ability to plan problem solving at 71.42%, and 3) ability to do counting at 75.61%.